2019
DOI: 10.1088/1742-6596/1179/1/012174
|View full text |Cite
|
Sign up to set email alerts
|

LC 50 of Rind Durian (Durio zibethinus murr) Extract to Mortality of Aedes aegypti Larvae

Abstract: One of durian parts is its rind which contains essential oil, flavonoid, saponin, cellulose, lignin, as well as 11 starch content. Those content can be used as a larvacide against Aedes aegypti larvae. The aim of this research is to analysis LC50 of durian rind extract to mortality of Aedes aegypti larvae. In this research, we used the experimental method. Aedes agypti larvae are 440 larvae instar III divided into 12 groups which are negative control, positive control, durian rind extract with a concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Likewise, research conducted by Sumitha Samuggam, et al (2018) 31 using durian seeds found that LC 50 = 3.03 mg/mL (3030 mg/L). as well as research conducted by Arrizqiyani T, et al (2019) 24 using durian peel extract found that the LC50 of durian peel (Durio zibethinus murr) extract for the death of Aedes aegypti mosquito larvae was 7.76%.…”
Section: Antimicrobial Activity and Lc50 In Durian Plantsmentioning
confidence: 86%
“…Likewise, research conducted by Sumitha Samuggam, et al (2018) 31 using durian seeds found that LC 50 = 3.03 mg/mL (3030 mg/L). as well as research conducted by Arrizqiyani T, et al (2019) 24 using durian peel extract found that the LC50 of durian peel (Durio zibethinus murr) extract for the death of Aedes aegypti mosquito larvae was 7.76%.…”
Section: Antimicrobial Activity and Lc50 In Durian Plantsmentioning
confidence: 86%
“…The last product of composting were liquid compost and solid compost which reach up to 80 % of total product. The rest of 20 % product was waste material that used for another purposed with specific processed, included biopesticides [9]. Amount 1 t material resulted 100 L of liquid organic compost (fertilizer) and ± 50 kg solid material.…”
Section: Fig 1 Scheme Of Processing Durian Rind Decomposition In Micmentioning
confidence: 99%